Hirtle Callaghan & Co - Elias, Jaan, (SAGE Business cases., 2020)
In August 2019, Stephen Vaccaro, Yale MBA '03, became the director of private equity at Hirtle, Callaghan & Co., LLC (HC), a leading investment management firm associated with pioneering the outsourced chief investment office (OCIO) model for college endowments, foundations, and wealthy families. Vaccaro, who would work under the guidance of Deputy CIO Dan McCollum (Columbia MBA '03), was tasked with spearheading efforts to grow HC's private equity (PE) market value from $1 billion to a new target of roughly $3 billion in order to contribute to the effort of generating higher long-term returns for clients. These new allocations, approved recently by HC's senior team, represented a sizable shift in HC's commitment to PE-from roughly 6% to 18% of the firm's more than $17 billion in assets under management (AUM).